Design of Activated Carbon/Activated Carbon Asymmetric Capacitors - Piñeiro-Prado, Isabel; Salinas-Torres, David; Ruiz-Rosas, Ramiro; Morallón, Emilia; Cazorla-Amorós, Diego (Frontiers in Materials, 2016)
Supercapacitors are energy storage devices that offer a high power density and a low energy density in comparison with batteries. Their limited energy density can be overcome by using asymmetric configuration in mass electrodes, where each electrode works within their maximum available potential window, rendering the maximum voltage output of the system. Such asymmetric capacitors must be optimized through careful electrochemical characterization of the electrodes for accurate determination of the capacitance and the potential stability limits. The results of the characterization are then used for optimizing mass ratio of the electrodes from the balance of stored charge. The reliability of the design largely depends on the approach taken for the electrochemical characterization. Therefore, the performance could be lower than expected and even the system could break down, if a well thought out procedure is not followed. In this work, a procedure for the development of asymmetric supercapacitors based on activated carbons is detailed. Three activated carbon materials with different textural properties and surface chemistry have been systematically characterized in neutral aqueous electrolyte. The asymmetric configuration of the masses of both electrodes in the supercapacitor has allowed to cover a higher potential window, resulting in an increase of the energy density of the three devices studied when compared with the symmetric systems, and an improved cycle life.